2007
DOI: 10.1097/01.prs.0000279374.99503.89
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Resonance Imaging and Explantation Investigation of Long-Term Silicone Gel Implant Integrity

Abstract: Although these results cannot necessarily be extrapolated to other implant types and manufacturers, they provide further information about the natural history of implant integrity, better enabling us to counsel prospective and current implant recipients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(11 citation statements)
references
References 15 publications
1
10
0
Order By: Relevance
“…Reasons for further exclusion are described in Figure 3. Eight studies examined both ultrasound and MRI,2936 5 evaluated US only,3741 and 8 evaluated MRI only 4249…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Reasons for further exclusion are described in Figure 3. Eight studies examined both ultrasound and MRI,2936 5 evaluated US only,3741 and 8 evaluated MRI only 4249…”
Section: Resultsmentioning
confidence: 99%
“…All 21 studies were diagnostic cohort studies 2936, 4249 Table 3. summarizes characteristics of the included studies.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…10,31 Studies have shown variation in operators to range for sensitivity from 71% to 86%, and for specificity from 48% to 95%. 32 Despite these small studies, ultrasound is still recommended as a highly effective tool in varying hands, provided a careful methodological approach is followed, and knowledge of pitfalls is considered. 33 Based on our findings we would recommend that PIP implant explantation should not be offered solely on the basis of patient history and clinical impression, as is currently recommended.…”
Section: Discussionmentioning
confidence: 99%